Keberhasilan sambungan pada beberapa jenis batang atas dan famili batang bawah kakao (Theobroma cocoa L.). (Grafting performance of some scion clones and root-stock family on cocoa (Theobroma cocoa L.) - Indah Anita Sari; Agung Wahyu Susilo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2012)
Differences in performance of grafting seedling were estimated from effect of using the root-stock and scion clones. This research aimed to study the differences of performance of some root-stock and scion clones on grafting seedling. The study used split plot design. First factor was root-stock consisted of ICS 60, Sca 6, Sca 12 and KW 165 and the second factor were 12 scions clones consisted of ICCRI 01, ICCRI 04, ICCRI 05, DR 2, Sulawesi 1, Sulawesi 2, KW 516, KW 514, KW 617, KW 570, KEE 2, and KW 604. There were three replication in each treatment and each replication consisted of 15 samples. Viability, lingkage diameter, ratio of root-stock and scion, hight of shoot, number of leaves and shoot were observed. The study showed that differences of root-stock just affected viability, lingkage diameter, and high of shoot. Scion clones factor affected to all of the characters. Their interaction caused the differences of all characters except of the number of shoot. Root-stock Sca 6 showed the lowest viability and number of the shoot, however root-stock KW 165 and ICS 60 showed the best performance to all parameters. The cluster analysis was done based on growth parameters and viability on lingkage distance of 15. There were three clusters; cluster 1 (KW 570), cluster 2 (ICCRI 04, ICCRI 05, Sulawesi 1, Sulawesi 2, KW 514, KW 165) and cluster 3 (ICCRI 01, DR 2, KW 516, KW 617, KW 604). Correlation analysis showed that main factor which affected the high viability root-stock diameter and diameter ratio of root-stock and scion were used.